Physical, Chemical and Biological Properties of Aspergillus salvadorensis discovered at the University of El Salvador - Vásquez Hidalgo, Antonio (International Journal of Molecular Microbiology, 2026)
The analysis of the physicochemical and biological properties of Aspergillus salvadorensis, obtained through DNA sequencing carried out by MACROGEN Inc. (South Korea, 2024), reveals an organism with a key ecological role and a complex network of metabolic and defense pathways. As a saprophytic decomposer, it efficiently degrades dead organic matter, including leaves, wood, and plant debris, and contributes to the recycling of carbon, nitrogen, and minerals, favoring the formation of humus and the natural improvement of the soil. Its metabolism stands out for its ability to break down polysaccharides through glucanases and cellulases and for sustaining energy processes such as heme synthesis, inositol metabolism, and mitochondrial transport. At the cellular level, it integrates pathways such as apoptosis and cell cycle, essential for regulating cell death programmed to stress, hyphal growth, and conidia production, in addition to using meiosis pathways for the formation of ascospores. Cytoskeleton-associated pathways explain the intracellular transport and polarity that enable directed growth. Against oxidative stress, it deploys a robust defense based on melanin and antioxidant pigments, along with enzymes such as catalases, glutathione peroxidases, peroxiredoxins, and thioredoxins. These act in conjunction with cell wall reinforcement, the MAPK (HOG) pathway, calcineurin, PKC, Yap1, and Atf1 transcription factors, and protective metabolites such as mannitol and trehalose. Additional mechanisms, such as DNA repair, chaperones, and proteasomes, ensure survival under stress. In conclusion, A. salvadorensis employs a wide range of enzymes, proteins, and secondary metabolites that ensure its resistance and adaptation in oxidative stress environments.